An efficient Photobioreactors/Raceway circulating system combined with alkaline-CO2 capturing medium for microalgal cultivation. (October 2018) - Kuo, Chiu-Mei; Jian, Jhong-Fu; Sun, Yu-Ling; Lin, Tsung-Hsien; Yang, Yi-Chun; Zhang, Wen-Xin; Chang, Hui-Fang; Lai, Jinn-Tsyy; Chang, Jo-Shu; Lin, Chih-Sheng
Graphical abstract: Highlights: A novel PBRs/Raceway circulating (PsRC) system was established for microalgal culture. High efficiency of microalgal growth and CO2 fixation by PsRC system was evaluated. Alkaline medium used in PsRC system can doubly enhance biomass productivity. CO2 fixation at 1.2 kg d −1 was observed in a 10-ton scale outdoor PsRC system. CO2 utilization efficiency of 50% was observed in a 10-ton scale outdoor PsRC system. Abstract: High efficiency of microalgal growth and CO2 fixation in a Photobioreactors (PBRs)/Raceway circulating (PsRC) system combined with alkaline-CO2 capturing medium and operation was established and investigated. Compared with a pH 6 medium, the average biomass productivity of Chlorella sp. AT1 cultured in a pH 11 medium at 2 L min −1 circulation rate for 7 days increased by about 2-fold to 0.346 g L −1 d −1 . The maximum amount of CO2 fixation and CO2 utilization efficiency of Chlorella sp. AT1 could be obtained at a PBRs to Raceway ratio of 1:10 in an indoor-simulated PsRC system. A similar result was also shown in an outdoor PsRC system with a 10-ton scale for microalgal cultivation. Under the appropriate circulation rate, the stable growth performance of Chlorella sp. AT1 cultured by long-term semi-continuous operation in the 10-ton outdoor PsRC system was observed, and the total amount of CO2 fixation was approximately 1.2 kg d −1 with 50% CO2 utilization efficiency.